Epidemiology and Management of Gynecological and Breast Cancers in the Two Reference Hospitals of Parakou, in North Benin - OBOSSOU, Awadé Afoukou Achille; TOGNIFODE, Véronique; BRUN, LUC; BALLEY, M.; DENAKPO, Justin Lewis; HOUNKPATIN, BENJAMIN IGNACE BODOUNRIN (My University, 2017)
Objective: It’s aim at describing the epidemiological features and management modalities of gynecological and breast cancers in Parakou in 2016. Framework and study method: It was a retrospective descriptive and analytical study covering a six-year period running from January 1, 2010 to December 31, 2015. It took place in Parakou at the University-affiliated Hospital of Borgou Department and at Boko Zone Hospital. Results: Of the 90 cases of gynecological and breast cancers recorded during this period, cervical cancer was the leading one with 54.44%. Breast cancer accounted for 34.44%, followed by ovarian cancer (5.57%). The median time from the onset of first symptoms to first consultation was 92 ± 71 days. The mean age of patients was 45 ± 15.9 years. Most cancers were diagnosed at an advanced stage (stage II, III or IV) that’s 60.43%. The most common anatomopathological types were: invasive ductal carcinomas (67.74%) for the breast andinvasive squamous cell carcinomas for the cervix (66%). Surgical treatment is always the only therapeutic mean available. Conclusion: Gynecological and breast cancers are common in northern Benin. The treatment remains essentially surgical. It’s necessary to promote the early detection of these pathologies.
Keywords: Gynecological and breast cancers; Epidemiology; Parakou; Benin